2021
DOI: 10.3390/met11071039
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Stress Cracking Behaviour in Dissimilar Welded Joints of Duplex Stainless Steel and Carbon Steel

Abstract: As the need for duplex stainless steel (DSS) increases, it is necessary to evaluate hydrogen stress cracking (HSC) in dissimilar welded joints (WJs) of DSS and carbon steel. This study aims to investigate the effect of the weld microstructure on the HSC behaviour of dissimilar gas-tungsten arc welds of DSS and carbon steel. In situ slow-strain rate testing (SSRT) with hydrogen charging was conducted for transverse WJs, which fractured in the softened heat-affected zone of the carbon steel under hydrogen-free c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Figure 7h shows the formation of cracks inside the ferrite cleavage facets [37]. The low presence of ductile microvoids indicated that there was little tearing through γ-phase, supporting the idea of a more brittle α-phase coinciding with the higher density of cleavage facets [42]. As previously seen, the sites where the cracks nucleated were the inclusions, which appeared to be cracked in a brittle manner (see Figure 7i).…”
Section: Fractographic Studysupporting
confidence: 66%
“…Figure 7h shows the formation of cracks inside the ferrite cleavage facets [37]. The low presence of ductile microvoids indicated that there was little tearing through γ-phase, supporting the idea of a more brittle α-phase coinciding with the higher density of cleavage facets [42]. As previously seen, the sites where the cracks nucleated were the inclusions, which appeared to be cracked in a brittle manner (see Figure 7i).…”
Section: Fractographic Studysupporting
confidence: 66%
“…2 Steel may be subject to hydrogen ingress during the welding process, and the welded joints may be prematurely damaged due to the damaging effects of hydrogen in long-term service in the hydrogen-containing environment. In recent years, most of the relevant existing works are about the effect of hydrogen on the mechanical properties of welded joints, such as Pan et al 3 studied the effect of hydrogen on the SCC of 2205 DSS simulated weld microstructure, Park et al 4 investigated the hydrogen stress cracking behaviour in dissimilar welded joints of DSS and carbon steel, and Fu et al 5 investigated the effect of hydrogen atoms on the SCC behaviour of SUS301L-MT stainless steel laser arc hybrid welded joints, while studies on the effect of hydrogen on the pitting behaviour of DSS welded joints are only sporadic. Therefore, it is essential to assess the effect of hydrogen on the pitting behaviour of DSS welded joints.…”
Section: Introductionmentioning
confidence: 99%
“…Even minimal concentrations of hydrogen can lead to the embrittlement of metals and alloys. This embrittlement significantly diminishes their mechanical properties, thereby posing risks to the structural integrity and safety of the pipelines [11][12][13]. When hydrogen gas is transported through pipelines, it adsorbs and diffuses into the metal, altering the metal lattice structure.…”
Section: Introductionmentioning
confidence: 99%